Vaginal synechiae in reproductive woman : A case report - Dinata, Kurnia Ariya; Setia, Dyhan Purna; Putra, Ilham Rizka (Fakultas Kedokteran Universitas Andalas, 2022)
Background: Vaginal synechiae is a condition which lips of labia minor was fused and covered the opening of vagina. The choice of treatment depends on the age group and the thickness. The cause is multifactorial, but during childhood it can be caused by hypoestrogenism or trauma to the vulvar, Labial adhesion is one of the most common paediatric gynaecologic problems. In the post-delivery hypo-estrogenic state of the female infant, the labia minora stick together in the midline. Case Report: A 23-year-old woman complained of having a different genitalia appearance compared to her friends. Patient had menarche at 13 years old, with regular cycles for 4-5 days and using 2-3 pad/day on her period. Conclusion: Vaginal synechiae in this patient maybe multifactorial, but during childhood it can be caused by hypoestrogenism during pregnancy or trauma to the vulvar, Labial adhesion is one of the most common paediatric gynaecologic problems. Synechiae incision was performed in this patient. Topical antibiotic and steroid maybe needed to promote healing and prevent recurrence.